The role of MMP-1 and FGFR4-R388 gene polymorphisms in pituitary adenoma - Zlatkutė, Eglė; Liutkevičienė, Rasa; Vilkevičiūtė, Alvita; Glebauskienė, Brigita; Kriaučiūnienė, Loresa; Jakštienė, Silvija; Žaliūnienė, Dalia (Acta medica Lituanica, 2018)
Background. The pathogenesis of pituitary adenoma (PA) is complex and poorly understood. It is thought that PA has a multifactorial aetiology; genetic factors also have an impact on PA development. Since MMP1 and FGFR4 genes play an important role in tumour growth, differentiation and progression, we decided to determine if the frequency of the genotypes of MMP-1 and FGFR4-R388 polymorphisms influence the development of PA. Materials and methods. The study enrolled n = 100 patients with PA and n = 200 healthy controls (reference group). The genotyping tests of MMP-1 and FGFR4-R388 were carried out using the real-time polymerase chain reaction (PCR) method. Results. The polymorphism in the MMP-1 gene 1G/1G genotype was more frequent in the group of invasive PA than in the control group: 28.6% vs. 16.5%, p = 0.044. The 1G/2G genotype was more frequent in females of the control group compared to PA group females: 50.3% vs. 30.8%, p = 0.011. The polymorphism in the MMP-1 gene 1G/1G genotype was more frequent in the active PA group than in the control group: 28.4% vs. 16.5%, p = 0.044. FGFR4-R388 did not play any predominant role in PA development. Conclusion. The MMP-1 gene 1G/1G may play a role in invasive and active PA development.